Rethinking Institutional Strategies for Latin American Universities - Iván Moreno , Carlos; Enrique Flores, Jorge (International Higher Education, 2020)
Latin American (LATAM) universities rank low in the most influential rankings, which makes them internationally invisible. Competition in rankings requires vast resources. Focusing on niches and specific subjects may be a better alternative to gain legitimacy and boost the attractiveness of LATAM universities, and may facilitate partnerships with better-ranked universities, increasing their international prestige.